Why they fight? Reconsidering the role of motivation in combat environments. Issue 3 (3rd July 2019) - Pawiński, Michal; Chami, Georgina
ABSTRACT: The current combat motivation model based on primary group thesis assumes that the main force behind motivation is peer-bonding or otherwise known as unit cohesion. Cohesion is perceived as an all-encompassing factor that leads to satisfactory (or unsatisfactory in lack thereof) military effectiveness and performance in conflict environments. However, the article identifies three main problems with this perspective: 1. mono-dimensional view of motivation; 2. motivation based on heteronomy, and 3. self-reporting bias. The current model does not consider motivation as a separate entity from cohesion; it does not place motivation as fundamental human value; lastly, it takes motivation as granted by-product of socialization. The article proposes a new combat motivation model based on The Self-Determination Theory. The theory maintains that human motivation requires satisfaction of three psychological needs of competence, relatedness, and autonomy. The degree of satisfaction of those three needs leads to different types of regulated motivations – a continuum from intrinsic to extrinsic – each of which has specifiable consequences for learning, performance, and well-being of an individual.